2017
DOI: 10.3389/fnbeh.2017.00118
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HTTLPR Genotype Modulates Reactive Visual Scanning of Social and Non-social Affective Stimuli in Young Children

Abstract: Previous studies have documented the 5-HTTLPR polymorphisms as genetic variants that are involved in serotonin availability and also associated with emotion regulation and facial emotion processing. In particular, neuroimaging and behavioral studies of healthy populations have produced evidence to suggest that carriers of the Short allele exhibit heightened neurophysiological and behavioral reactivity when processing aversive stimuli, particularly in brain regions involved in fear. However, an additional disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The previous study indicated that the Caucasians with the SS genotype of 5-HTTLPR polymorphism rate impersonal harms as more impermissible (Marsh et al ., 2011), while we found that the Asians with the SS genotype rate impersonal harms as more permissible. For Caucasians, the enhancement of the S allele on permissibility rating may attribute to the allele’s roles in heightening the amygdala activation (Dannlowski et al ., 2010; Lonsdorf et al ., 2014; Cheon et al ., 2015; Kilpatrick et al ., 2015; Christou et al ., 2017). However, ethnic differences in the functions of S allele in amygdala activation should be noticed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study indicated that the Caucasians with the SS genotype of 5-HTTLPR polymorphism rate impersonal harms as more impermissible (Marsh et al ., 2011), while we found that the Asians with the SS genotype rate impersonal harms as more permissible. For Caucasians, the enhancement of the S allele on permissibility rating may attribute to the allele’s roles in heightening the amygdala activation (Dannlowski et al ., 2010; Lonsdorf et al ., 2014; Cheon et al ., 2015; Kilpatrick et al ., 2015; Christou et al ., 2017). However, ethnic differences in the functions of S allele in amygdala activation should be noticed.…”
Section: Discussionmentioning
confidence: 99%
“…However, ethnic differences in the functions of S allele in amygdala activation should be noticed. For example, the S allele heightens the reactivity of the amygdala in Caucasians (Dannlowski et al ., 2010; Lonsdorf et al ., 2014; Cheon et al ., 2015; Kilpatrick et al ., 2015; Christou et al ., 2017), while this allele decreases the reactivity of the amygdala in Asians (Lee & Ham, 2008; Li et al ., 2012; Long et al ., 2014). These findings may suggest that Asians with the S allele may show lower emotional aversion to harms than Caucasians with this allele.…”
Section: Discussionmentioning
confidence: 99%
“…Given the developmental constraints on coping efficacy, restricting attention to threatening stimuli is proposed to be one of the few viable strategies for managing heightened insecurity in early childhood (Bowlby, 1980; Bretherton & Munholland, 1999). For example, in a sample of 4- to 7-year-old children, Christou et al (2017) found that younger children exhibited greater attentional avoidance to negative stimuli. As adverse experiences become less overwhelming with development, it is possible that attentional avoidance to threats diminishes or even shifts toward sensitization as children age into adolescence (e.g., Gulley et al, 2014; Schermerhorn et al, 2015; Shackman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by the appearance of the circular matrix of adult faces (i.e., 1 emotion face, 5 neutral faces) displayed for 3500 milliseconds. Stimulus presentations of similar duration have been successfully used in previous research with preschool and early elementary school children (e.g., Christou, Wallis, Blair, Zeegers, & McCleery, 2017; Gamble & Rapee, 2009). After five practice trials, 24 target trials were conducted, with each of the target emotions (i.e., anger, sadness, fear) displayed eight times in random order.…”
Section: Methodsmentioning
confidence: 99%